Land use and landscape pattern changes in the Fenhe River Basin, China - Ying Zhao; Bingqing Zhao; Fei Wang (Scientific Reports)
Abstract The composition and pattern of ecosystems play a crucial role in determining the overall condition and spatial variations of ecosystem services. In this study, we explored the Normalized Difference Vegetation Index (NDVI), six land use/land cover change (LULC) types, and their landscape patterns to reflect spatial-temporal dynamics from 2010 to 2020 in the upper and middle reaches of the Fenhe River Basin. The trend analysis of Mann-Kendall tests was used to assess the NDVI variation of each pixel over the past decade. Shannon’s Diversity Index (SHDI) was used to quantify the complexity of the landscape pattern of local LULC. Meanwhile, the spatial-temporal dynamic variations of vegetation NDVI and six LULC types were illustrated using geographic mapping methods. The results were presented as follows: (1) From 2010 to 2020, vegetation cover increased, with an annual NDVI increment of 0.003 (P < 0.001). Spatially, there was a significant increasing trend in NDVI, particularly in high-altitude mountainous areas where the vegetation cover mostly consisted of forests or grasslands. However, there was no significant change in vegetation cover in the low-lying urban agglomeration area. (2) During the period from 2010 to 2020, there was a significant decrease in the area of water bodies and wetlands, the rate of decrease slowed from 2015 to 2020. Specifically, the percentage of decrease from 2010 to 2015 increased by more than 14%. This proportion exceeded 30% when compared to the final governmental ecological management goal set during the 13th Five-Year Plan Period (2016–2020). (3) During the same period, the SHDI of LULC exhibited heterogeneous characteristics. In the high-altitude areas near the river basin boundary, SHDI values were below 1.0. Conversely, in the low-altitude plains and urban areas with frequent human activities, SHDI values exceeded 1.0, reaching above 1.5 in urban areas. This study provides a scientific reference for the construction and management of the ecological environment in the Fenhe River Basin, along with practice insights for ecological protection and high-quality development in the Yellow River Basin.